Effects of Digital Platform Openness on Recognition of Entrepreneurial Opportunities and Integration of Entrepreneurial Resources - Dan Li; Kang Li (Discrete Dynamics in Nature and Society)
Drawing on the theories of open innovation and entrepreneurship, this paper discusses the action mechanism of digital platform openness (DPO) on the recognition of entrepreneurial opportunities (EOR) and the integration of entrepreneurial resources (ERI) and explores the boundary conditions of this mechanism. Several hypotheses were put forward and verified by analysing 302 valid questionnaires. The results show that the breadth and depth of DPO positively affect EOR and ERI; these positive effects are positively moderated by the service level of the digital platform. The research findings provide a reference to digital platform enterprises to decide on platform opening strategy and platform service optimization.